2021
DOI: 10.3390/sym13071134
|View full text |Cite
|
Sign up to set email alerts
|

A Discontinuity of the Energy of Quantum Walk in Impurities

Abstract: We consider the discrete-time quantum walk whose local dynamics is denoted by a common unitary matrix C at the perturbed region {0,1,⋯,M−1} and free at the other positions. We obtain the stationary state with a bounded initial state. The initial state is set so that the perturbed region receives the inflow ωn at time n(|ω|=1). From this expression, we compute the scattering on the surface of −1 and M and also compute the quantity how quantum walker accumulates in the perturbed region; namely, the energy of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…For DPs, thus generated or annihilated around point-like singularities in a given material (a mathematically simplified model of a dopant), a phonon field, as the quantized lattice oscillations, works as their dynamical environment; thus, the goal of DP dynamics would describe DPs' behaviours, i.e., coupling with the environmental phonon field, with their "entries" and "outlets" at singular locations. Since a DP has a highly localized spatial structure, several researchers collaborating with RODreP, for instance, Hamano and Saigo [32], Konno et al [33] and Higuchi et al [34], are now developing models that describe DP behaviours by employing quantum walk approaches.…”
Section: New Dynamical Model Of Dpsmentioning
confidence: 99%
“…For DPs, thus generated or annihilated around point-like singularities in a given material (a mathematically simplified model of a dopant), a phonon field, as the quantized lattice oscillations, works as their dynamical environment; thus, the goal of DP dynamics would describe DPs' behaviours, i.e., coupling with the environmental phonon field, with their "entries" and "outlets" at singular locations. Since a DP has a highly localized spatial structure, several researchers collaborating with RODreP, for instance, Hamano and Saigo [32], Konno et al [33] and Higuchi et al [34], are now developing models that describe DP behaviours by employing quantum walk approaches.…”
Section: New Dynamical Model Of Dpsmentioning
confidence: 99%
“…The frequency is described by ξ ∈ R/2πZ. In [13], the comfortability to the frequency for quantum walker on the finite path is computed: it is shown that the quantity of the comfortability can be tuned between O(1) and O(M 3 ), where M is the length of the path, by adjusting the frequency ξ. In this paper, we consider more detailed information of the comfortbility on the path; that is,…”
Section: Introductionmentioning
confidence: 99%